Design and implementation of a solar powered kit for measurement and logging of environmental parameters using the SEN55 sensor - J. Nchi Muhvu; M.D. Fendji; C.M. Ekengoue (Measurement: Energy)
Air pollution poses significant threats to human health, ecosystems, and biodiversity, exacerbating climate change and reducing life expectancy. This study presents the design and implementation of a 6 W, 5 V solar-powered air quality monitoring system using the SEN55 environmental sensor node. The device measures particulate matter (PM1, PM2.5, PM4, PM10), humidity, temperature, volatile organic compounds (VOC), and nitrogen oxides (NOx), with data logged via an ATmega2560 microcontroller and displayed for real-time visualization. Field tests conducted in urban (Muea) and peri-urban (Awae-Ewangkang) areas in Cameroon revealed significant differences in air quality. Muea showed higher PM and humidity levels, exceeding recommended thresholds, while Awae-Ewangkang demonstrated better air quality but elevated humidity. Investigations highlighted the severe air pollution caused by traditional lighting sources such as kerosene lamps and candles. The device's sensitivity and reliability in identifying pollution hotspots were validated, emphasizing the potential health risks associated with these sources. The study underscores the device's ability to enhance environmental awareness, guide public health initiatives, and promote sustainable alternatives like solar energy systems. This novel system contributes to advancing air quality monitoring, offering a scalable and impactful solution for reducing pollution and safeguarding health.